Levels of Secondary School Teachers’ Leadership and Perceived Support from the School Management in Juban I and II Districts - Desabayla, Ryan (Papanda Publisher, 2024)
Teacher leadership is needed in every learning institution. It empowers teachers to play proactive roles in shaping educational settings. The researcher of this study determined the levels of secondary teachers’ leadership and perceived support from the school management and utilized a quantitative descriptive survey design and used adopted questionnaire. The study subjects were 64 secondary school teachers in Juban I and II Districts. The distribution of participants was as follows: six from Olimpio A. Guarin Jr. National High School, five from Lajong National High School, one from Biriran National High School, six from Guruyan National High School, 44 from Juban National High School, and two from Sablayan National High School, and the data were collected through Google Forms. Moreover, the researcher utilized the weighted mean and Pearson correlation coefficient in analyzing the gathered data. Findings revealed that the secondary school teachers agreed (3.65) on the level of teacher leadership and agreed (3.55) on the level of school management support as perceived. Furthermore, there was a weak relationship between the levels of secondary school teachers’ leadership and perceived support from the school management. The researcher recommended that the leadership levels of secondary school teachers in Juban I and II districts should be sustainably promoted and enhanced. Support from school management for teacher leadership is essential. There should be a strong relationship between teachers and school management to achieve effective leadership. Additionally, action research should be conducted to improve teacher leadership and school management in the Juban I and II districts.